Expectations of Generation Z in the World of Work Towards a Golden Indonesia 2045 - Sulistyorini, Ninik; Puspitasari, Dina; Khasanah, Alvy; Perdhana, Mirwan Surya (LifeSciFi, 2024)
It is known that each generation entering the world of work has a different character and mindset. Generation Z born between 1995 and 2012 where in this era, information technology developed rapidly. This generation has begun to enter the world of work. There are concerns about companies' ability to attract and retain this new generation. Companies that want to attract talent from Generation Z must understand their needs. The aim of this qualitative research is to explore the expectations of the university-educated Generation Z in the world of work in Indonesia, who have recently entered or will soon enter the labour market. The focus of this research is what Generation Z is looking for in the world of work in order to realize a Golden Indonesia 2045. This research uses Interpretative Phenomenological Analysis (IPA). Interviews were conducted with 10 (ten) college alumni at several universities spread across Semarang and its surroundings. This research is useful for employers in helping them better understand this new group and help initiate changes to their recruitment processes in the coming period.